Soffitti figurati nelle chiese di Roma - Conforti, Claudia (Opus Incertum, 2018)
The late-renaissance and baroque churches of Rome frequently show coffered wooden ceilings with relief figures of saints. The essay focuses on those plastic figurations, linking them with both the outcomes of the Council of Trent concerning the catechistic use of images and the new religiosity propagated by the Counter-Reformation. Among those ceilings the essay investigates the one at San Lorenzo in Damaso (1587), dismantled in the nineteenth century, which depicts in bas-relief the glory of the Martyr and some episodes of his life. Before the ceiling of San Lorenzo, this type of figuration was limited to symbolic, iconic and laconic elements, eloquent but not dramatic, as in the magnificent ceilings of San Giovanni in Laterano and, in part, of the Ara Coeli, both executed by the famous French lignarius Flaminio Boulanger.